Increased monocyte abundance as a marker for relapse after discontinuation of biologics in inflammatory bowel disease with deep remission - Kwon, Yiyoung; Kim, Yoon Zi; Choe, Yon Ho; Kim, Mi Jin (Frontiers in Immunology, 2022)
Monocytes are involved in the upstream inflammatory process in the immune reaction in inflammatory bowel disease (IBD). Patients with IBD who discontinued biologics have been found to relapse, even after checking for deep remission. This study investigated whether monocytes could act as a predictor of relapse in patients who experienced relapse after the discontinuation of biologics. To this end, pediatric patients (<19 years old, n = 727) diagnosed with IBD from January 2003 to December 2021 were retrospectively reviewed. Clinical features, monocytes, and disease activity at the time of discontinuing biologics were evaluated by dividing patients into a relapsed group and a non-relapsed group after discontinuing biologics. The percentage of monocytes (8.65% vs. 6.42%, P < 0.001), the absolute monocyte count (614.79 cells/μL vs. 381.70 cells/μL, P < 0.001), and the monocyte/polymorphonuclear leukocyte (PMN) ratio (0.18 vs. 0.11, P < 0.001) at the time of discontinuation were significantly higher in patients who experienced relapse. As a result of multivariate analysis, the monocyte percentage (odds ratio: 2.012, P < 0.001) and monocyte/PMN ratio (odds ratio: 4.320E+14, P = 0.002) were evaluated as risk factors for relapse. Diagnostic capability was confirmed using area under operating characteristic curve (0.782) of the monocyte percentage for assessing the relapse within 6 months with cutoff value of 8.15% (P < 0.001). The findings presented in this study indicate that the patients with high monocyte counts experienced relapse after the discontinuation of biologics. A monocyte percentage of over 8.15% in the blood at the time of discontinuation was found to be associated with a high probability of relapse within 6 months, even in deep remission.